ANALISIS KETERPADUAN PASAR CABAI RAWIT (CAPSICUM FRUTESCENS L) MENGGUNAKAN ECM DI PROVINSI BENGKULU - Asef Asef; Redy Badrudin; Sriyoto Sriyoto (Jurnal AGRIBIS, 2023)
ABSTRACT This research is an integrated market "Chili Rawit" in Bengkulu Province. The districts analyzed were Rejang Lebong, Kepahiang, Kaur, Mukomuko and Bengkulu Utara. The purpose of this research is to analyze the horizontal market integration of Cayenne Pepper or "Chili Rawit". The data used is secondary data, namely data on the price of cayenne pepper in Bengkulu Province per month and was taken for the last 3 years, from 2016 to 2018. The analysis was carried out descriptively for price behavior and to analyze horizontal market integration using the Eviews 7 application shows that the price development in the variation in the price of cayenne pepper that occurs between Rejang Lebong Regency and the other four districts is high and unstable, the price development in these five districts fluctuates due to factors influencing demand and supply, while the horizontal market integration of cayenne pepper in Bengkulu Province is already integrated. Based on the results of market integration analysis between the price of cayenne pepper in Rejang Lebong Regency as a producer and in Kepahiang, Kaur, Mukomuko District, Bengkulu utara as retailers in Bengkulu Province, it shows that there is integration. This is indicated by the results of the cointegration test on the residual value of the regression of the two stationary variables. Keywords: Price Behavior, Horizontal Market Integration.